Managing Geo-Based Challenges World-Wide Case Studies and Sustainable Local Solutions - Baban, Serwan M. J. (Environmental Science, 2014)
This book  provides sound conceptual understanding of the current approach to management and decision making regarding geo-based challenges in developing countries that tend to suffer from information poverty and subjectivity, and are reactive. The book also provides the necessary technical tools to energize research thinking and develop locally driven practical and sustainable solutions, ultimately moving management and decision making from being reactive to being proactive. This book fills a void as there are no published books to show the way forward or to present real case studies for this purpose. Case studies that utilize new technologies and scientific thinking are presented for developing sustainable management options based either on producing local applied research or on utilising relevant international research. These case studies are based on the author's first-hand experiences in arid/semi-arid (Iraq, Tunisia, Morocco, and Jordan), temperate (UK), and tropical environments (Malaysia, the Caribbean region, Indonesia, and Australia).